Penggunaan Kata Sapaan pada Percakapan Siswa SDN Langkang Lama Kecamatan Pulau Laut Timur Kabupaten Kotabaru - sri Juniati (STKIP Paris Barantai, 2020)
The purpose of this study is to describe the use of greeting words in the conversation of SDN Langkang Lama students in Kotabaru district? This type of research is the type of field research by presenting the data used in this study as a qualitative method. Because the data collected is in the form of words, picture sentences and not numbers. That was caused by the application of qualitative methods. Data sources in the implementation of this study were primary data and secondary data. Data collection techniques in this study by observation, recording, listening and note taking. And data analysis techniques namely data recording transcripts, data translators, data analysis and finally draw conclusions. The results showed that the use of greetings in students 'conversation at SDN Langkang Lama, Kotabaru Regency, namely the greeting words of respect found in students' greetings to greet teachers and greet other students found as many as 29% who were included in the classification is very low. In the usual greeting words found in the speech of students to greet the teacher and greet other students found as many as 32% included in the low classification. In rough greeting words found in the speech of students to greet the teacher or other students found as many as 39% included in the low classification .